FACTORS ASSOCIATED WITH ACADEMIC PERFORMANCE IN BASIC PROFESSIONAL COURSES AMONG NURSING STUDENTS AT HAI DUONG MEDICAL TECHNICAL UNIVERSITY (Vietnam Journal of Community Medicine, 2026)
Objective: To identify several factors associated with the academic performance in basic professional courses among nursing students at Hai Duong Medical Technical University during the period 2020–2023.Methods: A cross-sectional descriptive study was conducted on 283 nursing students from December 2023 to December 2024. The survey instrument included nine groups of factors: learning methods, learning motivation, perseverance, academic competition, learning goals, peer influence, teaching methods of lecturers, school impression, and facilities. The items were assessed using a Likert scale ranging from 0 to 4 points. Descriptive statistics and the Chi-square test were used to identify several factors associated with students’ academic performance.Results: Female students accounted for 91.17%; students from near-poor households accounted for 2.48%; and students with part-time jobs accounted for 19.08%. Factors associated with academic performance included learning methods, learning motivation, perseverance, and lecturers’ teaching methods (p < 0.05).Conclusion: Learning methods, perseverance, and teaching methods were associated with academic performance. It is necessary to enhance teaching method innovation and promote students’ active learning.
Keywords: Associated factors, academic performance, nursing students.